RANCANG BANGUN SISTEM PENGATURAN SUDUT PELUNCUR ROKET SECARA OTOMATIS BERBASIS KENDALI PID - , FATHAN ROZANI, Isnan Nur Rifa'i, S.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of control technology running so fast nowday. Rocket is one of the many technology that require control, control of the rocket is intended to determine the target point of the rocket. The rocket firing angle is absolutely necessary to determine the right target,for this reason need a angle controller that can make a right angle. PID (Proportional Integral derivative) is used as a regulator to determine the right angle at the rocket launcher with the PID Descrete with Euler's method. PID Descrete with Euler's method works like the accretion rate on fibonaci series, the previous output become the next step to determine the output. Euler's method can work without the transferfunction of a plant, because its value is changed dynamically and follow the reference of output error until set point is reached. Z-Transform is the theory of differential settlement of the step system whichis used to solve the differential equations in the time domain. PID tuning parameters on the system response must be in match with the limitations of the response sistem.Tuning is done on Proportional that serves as a positive response on the response acceleration, Integral as the accumulated value of the error so that the error reduction can take place quickly, and Derivative is acceleration control error for reduction it if too fast. Based on the PID tuning is done by looking at the nature of parameters in the PID parameters.